2005
DOI: 10.1108/ijsms-07-01-2005-b006
|View full text |Cite
|
Sign up to set email alerts
|

Celebrity or athlete? New Zealand advertising practitioners' views on their use as endorsers

Abstract: Substantial literature exists researching effective celebrity endorser characteristics, and a growing body of literature investigates the specifics of professional athlete endorsements. However, there has been little focus on selection from the advertising practitioner's perspective; research that does exist is limited to the United States and British markets. This research among New Zealand advertising agencies found that celebrities/athletes are used primarily to achieve' cut through' and that their use is g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 11 publications
0
43
0
Order By: Relevance
“…The results of the current study indicate that fans take notice when they see their favourite athlete advertising for that brand. So the athlete is causing brand awareness among his or her fans, which is a replication of the same idea that celebrity endorsers generate awareness of brands (Charbonneau & Garland, 2005). The attachment of an athlete with a certain brand spreads a positive message about the brand among the athlete's fans according to the responses of our participants.…”
Section: Discussionmentioning
confidence: 71%
“…The results of the current study indicate that fans take notice when they see their favourite athlete advertising for that brand. So the athlete is causing brand awareness among his or her fans, which is a replication of the same idea that celebrity endorsers generate awareness of brands (Charbonneau & Garland, 2005). The attachment of an athlete with a certain brand spreads a positive message about the brand among the athlete's fans according to the responses of our participants.…”
Section: Discussionmentioning
confidence: 71%
“…Limited information was the main reason to explore those dimensions. A large amount of literature was devoted to how effective endorser-audience and endorser product relationship influenced consumers (Charbonneau & Garland, 2005;Tingchi Liu, Huang, & Minghua, 2007;Jones & Schumann, 2000;Schaefer & Keillor, 1997). In this study, impacts of celebrity endorsement on different brand and product purchases had not been considered.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Charbonneau & Garland (2005) found that advertising practitioners in New Zealand placed greater importance on risk of negative publicity and hiring costs; by contrast, much of the consumer literature placed greater importance on credibility and trustworthiness. This may reflect the increasing costs of celebrity endorsements and the intense media interest in celebrity actions.…”
Section: Research Papermentioning
confidence: 99%
“…Four main studies have explored advertising practitioners' perspectives towards celebrity endorsements in the United States, the United Kingdom and New Zealand: Miciak & Shanklin (1994); Erdogan & Baker (1999,2000; Erdogan et al (2001);and Charbonneau & Garland (2005). Only the latter specifically investigated celebrity athlete…”
Section: Introductionmentioning
confidence: 99%